Molecular stratification of early breast cancer identifies drug targets to drive stratified medicine - Jane Bayani (Nature Portfolio, 2017)
Genetics: Expression signature identifies high-risk patients A gene expression signature identifies breast cancer patients who do poorly after endocrine therapy and might benefit from extra treatment. A team led by John Bartlett and Paul Boutros from the Ontario Institute for Cancer Research in Toronto, Canada, measured the activity levels of 165 genes known to be involved in breast cancer development in tumor samples from 3825 patients with early estrogen receptor-positive disease. The patients received either endocrine therapies (tamoxifen or an aromatase inhibitor) alone or additional chemotherapy as well. The researchers identified a 95-gene expression signature that, when combined with a determination of whether the cancer has spread into the lymph nodes, can help predict which patients are at high risk of disease progression, regardless of whether they received chemotherapy or not. These patients could be prioritized for additional drug therapies.